Kemampuan Membaca Cepat Berdasarkan Jenis Kelamin Siswa Kelas VIII SMP Negeri 03 Lebong Tahun Ajaran 2020/2021 - Fera Delva; Dian Eka Chandra Wardhana; Rokhmat Basuki (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The ability to read quickly is the ability of students to read quickly and with correct understanding. The better the students' ability to read quickly, the better the understanding of the reading content. However, it is not yet known whether there is a difference in speed reading abilities between male and female students against the text they read. For this reason, the purpose of this study was to describe the level of speed reading ability based on the gender of the eighth grade students of SMP Negeri 03 Lebong in the academic year 2020/2021. This research method using quantitative descriptive method. The population is 24 students and the sample is all members of the population, which is 24 students consisting of 12 male students and 12 female students. Based on the results of the study, it shows that the fast reading ability of female students of class VIII SMPN 03 Lebong is in the medium category and male students of class VIII of SMPN 03 Lebong are in the slow category while the fast reading ability of grade VIII students of SMPN 03 Lebong is in the medium category as a whole. The results of this study are expected to be an evaluation of Indonesian language teachers to continue to improve students 'speed reading skills, both male and female students so that students' literacy skills increase.